1995
DOI: 10.1148/radiology.196.3.7644631
|View full text |Cite
|
Sign up to set email alerts
|

Hand ischemia in patients with hemodialysis access grafts: angiographic diagnosis and treatment.

Abstract: In this group, symptoms were usually the result of inflow or outflow arterial disease, alone or in combination with graft steal. Transcatheter therapy (angioplasty or embolization) is effective in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 0 publications
1
65
0
6
Order By: Relevance
“…22 Flow-limiting disease distal to the fistula can be treated by angioplasty, 11 or by surgical bypass that may be part of a surgical revision of the fistula. Severe hand steal from a radiocephalic fistula due to reverse flow in the more distal radial artery can be treated by percutaneous radial artery embolization 12 or ligation (distal radial artery ligation, DRAL), 18,23 providing there is antegrade flow in the ulnar artery and an adequate palmar arch.…”
Section: Indications For Revascularizationmentioning
confidence: 99%
“…22 Flow-limiting disease distal to the fistula can be treated by angioplasty, 11 or by surgical bypass that may be part of a surgical revision of the fistula. Severe hand steal from a radiocephalic fistula due to reverse flow in the more distal radial artery can be treated by percutaneous radial artery embolization 12 or ligation (distal radial artery ligation, DRAL), 18,23 providing there is antegrade flow in the ulnar artery and an adequate palmar arch.…”
Section: Indications For Revascularizationmentioning
confidence: 99%
“…Using arteriography, the incidence of arterial stenosis in patients with peripheral ischemia has been reported to range from 62 to 100% (5,8 -10). In one study (8), complete arteriography from the aortic to the palmar arch was performed to assess the presence of arterial stenosis in HD patients who presented with symptoms of peripheral ischemia (n ϭ 13). It was found that 62% of the 13 patients who were referred for the evaluation of symptoms of steal syndrome demonstrated a significant (Ն50%) arterial stenosis.…”
Section: True Steal From the Forearm Arteriesmentioning
confidence: 99%
“…In one study, Valji et al (8) performed arteriography to evaluate patients with symptoms of hand ischemia. The entire arterial tree from the aortic arch to the palmar arch was evaluated.…”
Section: Percutaneous Interventionsmentioning
confidence: 99%
“…Although manual compression is a near-diagnostic test for the existence of the steal syndrome, the surgeon should always obtain a preoperative angiography of the entire arm before performing DRIL [7]. Such an angiography ought to be performed pre and post manual compressing of the AVA [17]. It will provide anatomic details regarding possible proximal and peri-access arterial stenosis and will also detail patency of the distal arterial tree.…”
Section: Resultsmentioning
confidence: 99%